Projection-Type Holographic Display With Observation Area Expanded Using Time-Division Reproduced Light Generation System - Tomoki Kanno; Yasuyuki Ichihashi; Takashi Kakue; Koki Wakunami; Ryutaro Oi; Tomoyoshi Shimobaba; Tomoyoshi Ito (IEEE Access)
Projection-type holographic displays are three-dimensional (3D) displays that utilize computer holography. These displays consist of a projection lens and a transparent holographic optical element (HOE) with off-axis concave mirror phase distribution and allow the user to observe a large 3D image by designing the magnification of the projection lens and the light-collecting function of the HOE screen independently. However, the observation area of the 3D image is limited. In this paper, we propose a method of expanding the observation area using time-division projection of multiple reproduced lights. With the proposed system developed to synchronize illumination lights and holograms, the proposed method can expand the observation area by a factor of 1.7 while maintaining the image size twofold that obtained by the conventional system. In addition, we succeeded in generating reproducing 3D video at 20 frames per second.